POLA KOMUNIKASI KELOMPOK AGAMA DALAM PENCEGAHAN PENYEBARAN UJARAN KEBENCIAN DI KECAMATAN MEDAN POLONIA PADA PEMILIHAN PRESIDEN TAHUN 2019 - Elok Perwirawati; Prietsaweny Riris T Simamora; Lestari Victoria Sinaga (Jurnal Darma Agung, 2019)
This research was inspired by many hate speech cases on social media that massively occurred ahead of the presidential election in 2019. The purpose of this study was to determine the communication patterns of religious groups in preventing the spread of hate speech and the group communication process carried out by religious leaders towards their groups about preventing the spread of hate speech in Medan Polonia District. This research uses a qualitative descriptive approach. The subjects of this study are religious leaders and members of their groups in Medan Polonia District. The sampling technique is by purposive sampling. The results showed that each religious group (Hindu, Protestant Christian, Buddhist and Islamic) had different communication patterns one to another. There are various ways conveyed by the religious leaders in minimalizing their religious members in expressing hate speech in social media. (1) Hindu religious groups tend to have relatively closed network communication networks in terms of politics to avoid the disunity the Hindu’s fellow and also urge their groups to enhance their group mutual respect. (2) The Buddhist group, in its worship process, did not touch the political issues and prefer to discuss issues of security and the economy. (3)Contastively, an open and active communication network is easily found in Christian groups who are oftenly tend to accommodate their group's development with circulation of hate speech on social media, for example by utilizing whatsapp applications, and discussed it in prayer groups. (4) However, religious leader of Islamic religious groups provide themselves as filters in their network communication to avoid any communication containing hate speech so that for his group religious leaders become role models / patrons to behave.